Inheritance Rights of Women in Makassar Society: A Study of Living Qur’an and its Implications for Islamic Law - Basri, Halimah; Miswar, Andi; Hasan, Hamka; Pabbajah, Mustaqim; Khalik, Subehan (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
The division of inheritance is one of the main problems in Islamic law. The legal basis for inheritance division refers to the Qur’an and hadith as the sources of law. However, there are different interpretations and practices in society regarding the division of inheritance for women and men. Here, this paper examines the practice of dividing the inheritance of women and men with the living Qur’an approach, and also maps out the forms of reception that occur in society and its implications for Islamic law. This qualitative study used the living Qur’an approach and collected the data by means of literature review and in-depth interview in three areas, namely Makassar City, Gowa and Bulukumba. The results of the study revealed that the people of Makassar have always divided inheritance based on the legal sources combined with customary law (adak). In this context, the community reception is grouped into three: first, the community that gives women the inheritance rights in accordance with the text in the Islamic law of a 2: 1 ratio (2 for male and 1 for female); second, the community that divides the inheritance through musyawarah (deliberation) and mufakat (consensus); and third, the community who carries out the inheritance settlement in court. In this case, however, the community tends to settle more through musyawarah and mufakat based on their customs and habits to maintain family integrity. This is because women are positioned with respect, while family problems including inheritance are part of siri' (shame). The division of inheritance to women from the point of view of the living Qur’an has an implication for flexible Islamic law as there is an integration of traditional Islamic teachings and culture within society.